Britain, Northern Rhodesia and the First World War - Yorke, Edmund James. author. aut Link
XXI, 337 p.
Keywords: An insightful account of the devastating impact of the Great War, upon the already fragile British colonial African state of Northern Rhodesia. Deploying extensive archival and rare evidence from surviving African veterans, it investigates African resistance at this time.